Hispanics in the U.S. labor market : selected research - Verdugo, Richard R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
The Hispanic population has emerged at the largest ethnic/racial minority in the United States, and has also become a major political constituency. Consequently, it is important to gauge the extent to which they have been integrated into various societal institutions. One important institution is the US labor market.The research contained in the present volume assess a number of issues about how well Hispanics are integrated into the US labor market, a major factor in the group's economic status. The research makes important contributions to the existing body of research on the Hispanic population, and may be used by scholars and policy makers in better understanding the status of this important ethnic/racial group.